Vol. 23 : Heat and Mass Transfer in the Thermal Control System of Technical and Technological Energy Equipment: April 22-23, 2015, Tomsk, Russia; [proceedings]; MATEC Web of Conferences - Kuznetsov G. V. Geny Vladimirovich; Strizhak P. A. Pavel Alexandrovich; Bulba E. E. Elena Evgenievna; Zhdanova A. O. Alena Olegovna (Les Ulis, 2015)
Title screen